Relational exchange in nonprofits: The role of identity saliency and relationship satisfaction. Issue 2 (19th June 2018) - Taylor, Jennifer A.; Miller‐Stevens, Katrina
Abstract : In practice and research pertaining to charitable giving, the emphasis has been on identifying the characteristics and motivations of donors, but few have asked why donors continue to support a particular nonprofit. This study examines the relationship between renewing donors and nonprofits and their impact on charitable giving levels using identity salience and relationship satisfaction as key mediators of nonprofit relational exchange. In a survey of 719 repeat donors in the United States, to a broad range of nonprofit organizations, identity saliency and relationship satisfaction are introduced as mediating constructs, and the results confirm that both constructs partially guide donor motivations and charitable giving. Theoretically, this suggests that the more a donor identifies with a nonprofit organization and the more satisfied the donor is in the relationship with the organization, the higher their intention to donate. This finding supports previous research in segmentation strategies and service‐dominant logic in the nonprofit sector. Managerial implications of this research include indication of a paradigmatic shift from relational exchange to transformational exchange (or value cocreation) in nonprofit organizations' approach to donor cultivation.